Identification of Radix Entomolaris and Modifications in Endodontic Treatment: A Clinical Approach and Case Report - Hamsaneni, Dileep (Journal of Contemporary Medical Practice, 2026)
Aim: To present a case of mandibular first molar with additional distolingual root (Radix Entomolaris). Summary: Endodontic therapy should result in complete debridement of root canal & provision of hermetic seal, to prevent re - infection. Mandibular 1st molars mostly present with two roots, mesial & distal. Anatomical variations may result in presence of an extra root, if present distolingually, k/a radix entomolaris (RE) or present mesiobuccally, k/a radix paramolaris. The first & foremost crucial step is careful interpretation of pre - operative radiograph. Multiple angled radiographs would result in detection of extra root/root canal, which would otherwise be missed due to superimposition. This case report describes endodontic management of mandibular molar with RE. Key Learning Points: 1) Detailed studying of pre - operative radiograph, taken at different angulations has to be done prior commencing the root canal therapy. 2) Modification in access cavity distolingually should be done to gain straight line access to the apex in case of RE. This will aid in unimpeded instrumentation. 3) Clinicians should be fully aware of the anatomical variations that might be present in mandibular 1st molars. 4) Extra canal is having curvatures & it’s mostly narrower in dimensions. therefore, pre - curving of initial file, establishing glide path play a crucial role in successful management of RE.